PECULIARITIES OF DESIGN OF SPECIAL CLOTHING FOR AMATEUR MOTORCYCLISTS - SARANA, OLEKSANDR; MAZNIEV, IEVGEN; ZASORNOV, ALEXANDER; VOROBIOV, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article is devoted to the development of a special protective suit for amateur motorcyclists. As a result of the analysis of the operating conditions of motorcyclists’ sportswear, the most negative environmental factors affecting the driver’s body are identified - wind speeds from 0 to 60 km/h, possible precipitation in the form of rain, blunt objects in case of fall. Clothing for amateur motorcyclists should protect the body from the effects of these negative factors, ease of use, comfort at rest and during intense movements. A characteristic feature of the operating conditions of sportswear for motorcyclists is that a person is almost always in a sitting position on a motorcycle. The method of non-contact optical determination of the main poses and characteristic movements of amateur motorcyclists is used in the work. To ensure a given level of ergonomic fit of the motorcyclist’s suit, it is proposed to use the following characteristics: the range of arms of the dressed person; resistance to accuracy and speed of movements; moving areas of clothing relative to the body when moving; tensile deformation of materials in parts, lack of free folds; horizontality of the bottom of the product, the correct position of the sleeve. The "thread method" was chosen to assess the ergonomic conformity of the clothing design. Using this method allows you to measure the amount of movement of individual parts of clothing and stretch material in garments and assess the dynamic compliance of clothing. To determine the air permeability of materials, it is proposed to use the calculation method, which involves determining the coefficient of air permeability by the nature of the weave, the number of threads on the warp and weft and the raw material composition. The areas of location of windproof and shockproof pads are determined. By setting the frequency of occurrence of structural elements and articulations of costumes of professional motorcyclists, the suit model is finally determined: jacket with a stand-up collar, a central zipper and a sewn-on strap, with reliefs; pants on a belt and with a relief. The design of the suit of amateur motorcyclists (sports jacket and pants) was built according to the method of "Mueller and Son". Further modeling of reliefs, yokes, cuffs and other structural elements was performed.